EVALUASI PROGRAM PEMBELAJARAN KEWIRAUSAHAAN SMA NEGERI 1 PREMBUN KABUPATEN KEBUMEN - Eko Putro Widoyoko; Sri Kustilah; Sri Endah Pamilih (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2020)
This study aims at determining the effectiveness of the entrepreneurship instructional program at SMAN 1 Prembun, Kebumen Regency in the academic year of 2018/2019. The evaluation model used is the EKO2P model. The population of the eleventh grade students majoring in social studies in the academic year of 2018/2019 consists of 156 students. The research sample of 101 students is determined based on the sample determination table by Isaac and Michael. Sampling is done by using a sample random sampling technique. Data collection instruments use the questionnaire method, document analysis, observation and interviews. Data analysis uses descriptive analysis The results showed that instructional quality gained a score = 2.95 belonging to good qualifications, instructional output obtained a mean score = 3.03 belonging to good qualifications, instructional outcomes obtained a mean score = 2.62 belonging to good qualifications. The overall score of the quality, output, and outcome of entrepreneurship instructional program was 2.87 belonging to good qualifications. Thus, it can be concluded that the entrepreneurship programs at SMA Negeri 1 Prembun in the academic year of 2018/2019 has been implemented successfully